Effect of Alq3 dopant on the optoelectronic parameters of NPD:Alq3 composite films - Mahmoud, Alaa Y. (Elsevier, 2021)
A comprehensive investigation has been performed to study the effect of tris(8-hydroxyquinoline) aluminum (Alq3) dopant on the optoelectronic parameters of N, N `-Di (1-naphthyl)-N, N `- diphenyl]-(1, 1 `-biphenyl)-4, 4 ` diamine (NPD). Composite films of NPD:Alq3 with different volumetric ratios were spun coated onto quartz substrates and their optical response was recorded by a UV-Vis spectrophotometer. It was found that the energy gap (Eg) of NPD can be easily tuned from 2.98 eV to 2.82 eV with the addition of Alq3. This doping process led to increase the value of dielectric constant and refractive index of NPD:Alq3 from 2.28 to 3.07 and 1.51 to 1.76, respectively. Wemple-DiDomenico (WD) model and Tauc's equation were utilized to determine and validate the energy gap of the investigated films. Noteworthy, the nature of optical transitions in NPD and NPD:Alq3 (1:1) films was confirmed to be direct forbidden, while for the other films it was direct allowed transition.